KEBIJAKAN DISKRIMINATIF TERHADAP KELOMPOK MINORITAS ROHINGYA DI MYANMAR - Hanifahturahmi, Hanifahturahmi (Universitas Riau, 2016)
Discriminative Policies to the Minorities Group of Rohingya in Myanmar. This paper isa research about â€œâ€why Myanmarâ€™s government has not recognized the status of the Rohingyawhile the issues of democratization underway in Myanmar and how the international communityâ€™sresponse (UNHCR) against the Myanmar governmentâ€™s attitude?.â€This research uses severalconcepts, including Democracy and National Character Building, Security, Responsibility to Protectand the distribution of power within a country. This research shows that the Myanmar governmenthas not recognized the Rohingyas because they do not want the sustainability of power of thegovernment of Myanmar uninterrupted in the future. The response of the international communityagainst the government of Myanmar came from the United Nations. The UN through UNHCR cango to Myanmar with the doctrine of Responsibility to Protect (RtoP). Serious human rights violationsin Myanmar led to high flows of refugees from Myanmar who disturb the national security of othercountries, especially Bangladesh and the countries located in the region of Southeast Asia.